2013
DOI: 10.1088/0004-637x/780/1/5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Sun's Polar Magnetic Fields With a Surface Flux Transport Model

Abstract: The Sun's polar magnetic fields are directly related to solar cycle variability. The strength of the polar fields at the start (minimum) of a cycle determine the subsequent amplitude of that cycle. In addition, the polar field reversals at cycle maximum alter the propagation of galactic cosmic rays throughout the heliosphere in fundamental ways. We describe a surface magnetic flux transport model that advects the magnetic flux emerging in active regions (sunspots) using detailed observations of the near-surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 33 publications
2
111
0
1
Order By: Relevance
“…During minimum years the vantage point effect is at least partly due to the latitudinally varying tilt of the high-latitude fields (Ulrich & Tran 2013), but appears in a different way in different data sets. Recently it has been shown that the vantage point effect appears very weakly, if at all, in the HMI data (Upton & Hathaway 2014). Accordingly, it may also depend on spatial resolution, the noise level of high-latitude measurements, and the errors in the calculation of field strength using different spectral lines.…”
Section: Measuring High-latitude Fieldsmentioning
confidence: 99%
“…During minimum years the vantage point effect is at least partly due to the latitudinally varying tilt of the high-latitude fields (Ulrich & Tran 2013), but appears in a different way in different data sets. Recently it has been shown that the vantage point effect appears very weakly, if at all, in the HMI data (Upton & Hathaway 2014). Accordingly, it may also depend on spatial resolution, the noise level of high-latitude measurements, and the errors in the calculation of field strength using different spectral lines.…”
Section: Measuring High-latitude Fieldsmentioning
confidence: 99%
“…Starting from the pioneering work of Wang et al (1989b,a), the surface flux transport (SFT) model has been made more sophisticated in several recent studies (van Ballegooijen et al 1998;Schrijver et al 2002;Baumann et al 2004Baumann et al , 2006Cameron et al 2010;Jiang et al 2014a; Upton & Hathaway 2014;Jiang et al 2015). In this model, recently reviewed by Jiang et al (2014b), one can study in detail how individual sunspot pairs contribute in building up the poloidal field and can address such questions as to how this process depends on such factors as the latitudinal positions of the sunspot pairs and the distribution in their tilt angles.…”
Section: Introductionmentioning
confidence: 99%
“…This entire process is better known as the Babcock-Leighton (BL) mechanism (Babcock 1961;Leighton 1969). The SFT models (Wang et al 1989(Wang et al , 2000van Ballegooijen et al 1998;Schrijver 2001;Mackay et al 2002aMackay et al , 2002bCameron et al 2010;Upton & Hathaway 2014;Hickmann et al 2015) are quite successful in capturing the physics of the BL mechanism. For the constant diffusivity, the magnetic field evolution on the solar surface is governed by the magnetic induction equation,…”
Section: Sft Methodologymentioning
confidence: 99%